Industrial Internet of Things Cybermanufacturing Systems - Jeschke, Sabina; Brecher, Christian; Song, Houbing; Rawat, Danda B.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Developing the core system science needed to enable the development of a complex industrial internet of things/manufacturing CPS (IIoT/M-CPS), this book will foster a research community committed to advancing research and education in IIoT/M-CPS and to transitioning applicable science and technology into engineering practice. Presenting the current state IIoT and the concept of cybermanufacturing, this book is at the nexus of research advances from the engineering and computer and information science domains. It features contributions from leading experts in the field with years of experience in advancing manufacturing. Readers will acquire the core system science needed to transform to cybermanufacturing that spans the full spectrum from ideation to physical realization.
Industrial Internet of Things and Cyber Manufacturing Systems -- An Application Map for Cyber-Physical Systems -- Cyber-Physical Electronics Production -- Cyber-physical Systems Engineering for Manufacturing -- Model-Based Engineering of Supervisory Controllers for Cyber- Physical Systems -- Formal Verification of SystemC-based Cyber Components -- Evaluation Model for Assessment of Cyber-Physical Production Systems -- CPS-based Manufacturing with Semantic Object Memories and Service Orchestration for Industrie 4.0 Applications -- Integration of a knowledge database and machine vision within a robot-based CPS.
Keywords: Manufactures; Application software; Telecommunication; Economic development; Electronic data processing -- Management; Machines, Tools, Processes; Computer and Information Systems Applications; Communications Engineering, Networks; Economic Development, Innovation and Growth; IT Operations